Effect of irrigation and nitrogen on growth and yield of sunflower (Helianthus annuus) - PRASAD, U K; PRASAD, T N; KUMAR, A (The Indian Journal of Agricultural Sciences, 2013)
An experiment on summer sunflower (Helianthus annuus L.) was conducted during 1994-96 with 4 irrigation levels basedon the ratio of irrigation watcr depth: cumulative pan evaporation (IW : CPE) and 4 nitrogen levels in Bihar. Theresults showed that seed yield increased significantly at IW : CPE ratio of 0.8 (1.49 tonnes/ha) with 6 cm depthcomprising of 6 irrigation. But water-use efficiency was higher at 0.6 ratio with 4 irrigation. Response to nitrogen Wasrecorded only up to 40 kg N/ha. Plant height, dry-matter/plant and capitulum diameter were maximum at 0.8 IW : CPE ratio.But I 000-seed weight increased only at [W : CPE of 0.6 and 40 kg N/ha. Total nitrogen uptake and net return were alsohighest at 0.8 IW : CPE ratio and 40 kg N/ha. Soil-moisture depletion was higher from 0-60 m layer with 4-6irrigation, whereas relative depletion in lower soil profile'(60-90 cm) was more in rain fed control.